Enamel demineralization around Orthodontic brackets bonded with new bioactive composite (in-vitro study) - Ali , Noor AM; Nissan , Layth MK; Khamis , Amar H; Al-Taai , Nameer (Journal of Baghdad College of Dentistry, 2024)
background: This study aimed to evaluate the effect of bioactive composite (ACTIVA) on enamel demineralisation when used as an orthodontic adhesive, compared to other adhesives. Materials and methods: Human upper premolars (n=64) were randomly divided into two equal groups; the first group stored the bonded teeth in deionised water for 30 days at 37°C, and the second group exposed the bonded teeth to acidic media. Each group was further subdivided into four subgroups, with eight premolars in each subgroup, based on the type of adhesive used to bond metal brackets: non-fluoride-releasing adhesive (Transbond XT), fluoride-releasing adhesive (Light Bond), light-cured, resin-reinforced glass ionomer (GC Fuji ortho LC), and bioactive restorative composite (ACTIVA BioACTIVE-RESTORATIVE). Enamel demineralisation was assessed at baseline and after 30 days with a laser fluorescence device (DIAGNOdent™ Pen). Results: There were significant differences in fluorescence variation values (ΔFV) among all four tested adhesive systems in both water and acid groups after 30 days. Light Bond adhesive showed the highest fluorescence variation value, while glass ionomer showed the lowest, indicating less enamel demineralisation around the bracket. ACTIVA had less enamel demineralisation in acidic media. However, there was no significant difference in enamel demineralisation between water storage and acidic media groups. Conclusion: ACTIVA (RMGIC + composite) exhibited less enamel demineralisation than Light Bond; however, Fuji ortho LC showed the lowest enamel demineralisation.